Modeling and Simulation of Flexible Transmission Mechanism with Multiclearance Joints for Ultrahigh Voltage Circuit Breakers - Fangang Meng; Shijing Wu; Fan Zhang; Zenglei Zhang; Jicai Hu; Xiaoyong Li (Shock and Vibration)
The transmission mechanism, of which the dynamic characteristics determine the reliability of the circuit breaker, is the principal component of the ultrahigh voltage (UHV) circuit breaker. The characteristics of transmission mechanism are quick motion, high sensibility, and high reliability. The transmission mechanism with multiclearance joints present strong no-linear vibration feature which strongly affects the reliability of the UHV circuit breaker. In this investigation, a planar rigid-flexible coupling model of the transmission mechanism considering the clearance joints and the flexibility of components is established by using ADAMS software. The dynamic contact model in clearance joints is performed, based on clearance vector model of clearance joint. Then, the reliability of the model is proved by means of comparing the results of experiments. The simulation results show that the dynamic response of the mechanism is greatly influenced by the clearance and the flexibility of components has a role of suspension for the mechanism. Moreover, the influence of the clearance size, input speed, and number of clearance joints on the dynamic characteristics of the mechanism are also investigated.